1988
DOI: 10.1056/nejm198806303182603
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Dipyridamole in the Prevention of Re-Stenosis after Percutaneous Transluminal Coronary Angioplasty

Abstract: To examine the role of antiplatelet therapy in the prevention of arterial restenosis after percutaneous transluminal coronary angioplasty (PTCA), we conducted a randomized, double-blind, placebo-controlled study in 376 patients. The active treatment consisted of an oral aspirin-dipyridamole combination (330 mg-75 mg) given three times daily, beginning 24 hours before PTCA. Eight hours before PTCA, the oral dipyridamole was replaced with intravenous dipyridamole at a dosage of 10 mg per hour for 24 hours, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0
10

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(164 citation statements)
references
References 25 publications
1
153
0
10
Order By: Relevance
“…Interestingly, despite standard aspirin and heparin therapy, leukocyte activation and platelet adherence still occur after coronary angioplasty. 32 In contrast, experimental data and preliminary clinical studies have suggested that antioxidants, such as vitamin E, may prevent restenosis after angioplasty. 33 Furthermore, in a large, double-blind, randomized trial, probucol, a well-known antioxidant, improved vascular remodeling after PTCA.…”
Section: Fontana Et Al 8-iso-pgf 2␣ and Neutrophil Adhesionmentioning
confidence: 99%
“…Interestingly, despite standard aspirin and heparin therapy, leukocyte activation and platelet adherence still occur after coronary angioplasty. 32 In contrast, experimental data and preliminary clinical studies have suggested that antioxidants, such as vitamin E, may prevent restenosis after angioplasty. 33 Furthermore, in a large, double-blind, randomized trial, probucol, a well-known antioxidant, improved vascular remodeling after PTCA.…”
Section: Fontana Et Al 8-iso-pgf 2␣ and Neutrophil Adhesionmentioning
confidence: 99%
“…Though the underlying processes have not yet been fully elucidated, a special role in promoting the migration and proliferation of smooth muscle cells has been advocated for adherent platelets and resulting mural thrombi. [3][4][5] While previous studies with antiplatelet and anticoagulant agents such as aspirin, 14) aspirin plus dipyridamole, 15) warfarin, 16) heparin, 17) thromboxane A 2 receptor antagonists, 18) and the thrombin inhibitor hirudin 19) did not demonstrate positive effects after PTCA, use of the glycoprotein IIb / IIIa antagonist blocking the final common pathway of platelet aggregation resulted in fewer early ischemic complications 20) and a lower frequency of clinical manifestations of restenosis. 21) However, no follow-up angiographic data are available.…”
Section: Discussionmentioning
confidence: 92%
“…Aspirin alone has little or no effect on angiographic or clinical restenosis, but longterm aspirin therapy is useful for secondary prevention of cardiovascular events. 23 However, lower doses of aspirin, 75-100 mg, are used in combination with other antithrombotic agents. This is because a higher dose of aspirin is associated with increased risk of bleeding when used along with clopidogrel, without any added benefit.…”
Section: Antiplatelet Medications For Desmentioning
confidence: 99%